Seasonal effects on the anatomy and histology of the reproductive tract of the male rodent mole Bathyergus Suillus Suillus (Schreber) - Van der Horst, G.(Gerhard) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1971.